Índice neutrófilo linfocito como prueba de tamizaje para la detección de periodontitis (2023)
Introduction: Periodontal disease is characterized by a series of inflammatory processes caused by microorganisms that lead to the destruction of periodontal tissue. The most common periodontal diseases are gingivitis and periodontitis. The dysbiosis of the subgingival biofilm, the host immune response and the presence of other risk factors (genetic, environmental) play an important role in the development of periodontitis. Materials and methods: The study included 20 systemically healthy patients, diagnosed with periodontitis, stage II onwards, who had 20 teeth present, these patients were treated at the UAN clinics, in addition to being certain about the presence of infections, an investigation will be made. by reviewing the anamnesis in the clinical history and verifying it in an interview with the patient. each patient was consulted if they wanted to take the blood count, this test was taken in a single laboratory in the city of ArmeniaQuindío, to have better specificity and less variability in the results. the type of study that was decided Cross sectional. Preliminary results: It was observed that the neutrophil/lymphocyte index count was higher in the group of patients with the presence of periodontal disease, compared to the group of patients without the presence of periodontal disease. It was possible to show that this index correlates positively with the periodontal parameters. Conclusion: The findings in this study favor the important role of the neutrophil/lymphocyte ratio, demonstrating that there is a relationship with periodontal disease, so it could be considered to use this ratio as a screening test for the detection of periodontitis. Keywords: Periodontitis, inflammation, complete blood count, index, lymphocytes, neutrophils